2016
DOI: 10.1016/j.susc.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk crystallization of amorphous solid water films: Confirmation of “top-down” crystallization

Abstract: The crystallization kinetics of nanoscale amorphous solid water (ASW) films are investigated using temperature-programmed desorption (TPD) and reflection absorption infrared spectroscopy (RAIRS). TPD measurements are used to probe surface crystallization and RAIRS measurements are used to probe bulk crystallization. Isothermal TPD results show that surface crystallization is independent of the film thickness (from 100 to 1000 ML). Conversely, the RAIRS measurements show that the bulk crystallization time incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The results for the "no cap" films show that the fraction-crystallized of the isotopic layer curves shift to longer times as the 5% D 2 O layer is placed farther away from the top of the film. The "no cap" results are consistent with our prior work, 36 which showed that the crystallization front propagates from the ASW/vacuum interface into the bulk. In this case, the crystallization of the isotopic layer is delayed until the crystallization front reaches the layer.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The results for the "no cap" films show that the fraction-crystallized of the isotopic layer curves shift to longer times as the 5% D 2 O layer is placed farther away from the top of the film. The "no cap" results are consistent with our prior work, 36 which showed that the crystallization front propagates from the ASW/vacuum interface into the bulk. In this case, the crystallization of the isotopic layer is delayed until the crystallization front reaches the layer.…”
supporting
confidence: 90%
“…Electronic addresses: Scott.smith@pnnl.gov and Bruce.Kay@pnnl.gov reflection absorption infrared spectroscopy (RAIRS) were employed to measure surface and bulk crystallization directly. 36 Those results clearly showed that the crystallization of ASW films in vacuum proceeds via a "top-down" mechanism. In the proposed mechanism, nucleation begins at the ASW/vacuum interface resulting in crystallization of the outer surface of the film.…”
mentioning
confidence: 92%
“…Understanding the kinetics and mechanism of amorphous ice crystallization is therefore crucial in mapping out astrophysical processes in the outer solar system. Consequently, the role of vapor-liquid interfaces in amorphous ice crystallization has been extensively studied [84][85][86][87][88][89]. The first major study was conducted by Backus et al [85,86], who utilized reflection absorption infrared (RAIR) spectroscopy and temperatureprogrammed desorption (TPD) spectroscopy to distinguish bulk and surface crystallization, respectively, and concluded that ASW nanofilms freeze via a 'top-down' mechanism, in which freezing starts close to the vaporglass interface.…”
Section: Freezing In Amorphous Ice Nanofilmsmentioning
confidence: 99%
“…As a result, their findings were questioned in later publications [87]. The most unequivocal evidence for surface freezing in ASW films was provided by Yuan et al [88], who preferentially placed isotopic layers of 5% D 2 O/95%H 2 O at different locations across a 1000-layer H 2 O ASW nanofilm, and used RAIR spectroscopy to probe its crystallization. They observed that the isotopic layer crystallized faster when it was located closer to the vapor-ASW interface.…”
Section: Freezing In Amorphous Ice Nanofilmsmentioning
confidence: 99%
“…Such ASW films are thermodynamically unstable and transform into crystalline ice (CI) at temperatures above ∼135 K on a laboratory time scale. The kinetics and mechanisms of this phase transition have been investigated by several researchers. The apparent activation energy for crystallization of ASW samples has been observed to be in the range of 60–77 kJ·mol –1 , , for which variations in the reported values may be related to the different rate-limiting steps in the investigated phenomena. Several researchers have studied the nucleation and growth steps of ASW crystallization separately by employing ingenious experimental schemes. , Dohnálek et al investigated the crystallization kinetics of thin ASW films deposited on a CI substrate and observed a dramatic acceleration of the crystallization rate at the ASW/CI interface, where only the growth step was required for crystallization to occur.…”
Section: Introductionmentioning
confidence: 99%